(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: to describe the characteristics of regional lymph node metastasis in ovarian cancer stages I-III and evaluate potential predictive factors for lymphatic spread in these cases. Materials and Methods: A perspective and prospective study comprises 62 patients diagnosed with ovarian cancer, initially treated with cytoreductive surgery from January 2023 to August 2024 at the Department of Gynecological Surgery, National Cancer Hospital. Results: The most common age group is 40-60 years (67.7 %). The avarage age at the time of diagnosis is 53.2±11.3 years. The majority of cases had High-grade Serous Carcinoma (HGSC) (62.9%). Preoperative MRI imaging characteristics: the detection rate of regional lymph nodes is 12.9%, with 75.0% of these nodes having a diameter ≥10mm. The proportion of disease stages II and III post-surgery (17.7% and 61.3%). The overall regional lymph node metastasis rates is 40.3%.,High-grade serous carcinoma has the highest rate of lymph node metastasis (80%). The test determines the cut-off level for lymph node size on CT/MRI to be 10mm, with a sensitivity of 80% and specificity of 67%. The lymph node metastasis rate in stage III is 43.8%, and in stage I, it is 40.7%. There were no patients with lymph node metastasis in stage II. The difference is not statistically significant (p > 0.05). Conclusion: In early-stage disease, thorough lymph node assessment is essential for precise staging, often necessitating systemic lymphadenectomy based on imaging diagnostics and intraoperative evaluation of visible lesions. For advanced stages, selective lymph node excision is advised on a case-by-case basis to achieve optimal surgical outcomes.